Grain refinement of Al-Mg-Sc alloy by ultrasonic treatment - Tuan, N. Q. (2015)
In foundry practice, ultrasonic treatment has been used as an efficient technique to achieve grain refinement in aluminium and magnesium alloys. This article shows the strong effect of pouring temperature and ultrasonic treatment at various temperatures on the grain refinement of Al-1 wt% Mg-0.3 wt% Sc alloy. Without ultrasonic treatment, a fine grain structure was obtained at the pouring temperature of 700 °C. The average grain size sharply decreases from 487 ± 20 to 103 ± 2 μm when the pouring temperature decreases from 800 to 700 °C. Ultrasonic vibration proved to be a potential grain refinement technique with a wide range of pouring tem- perature. A microstructure with very fine and homogeneous grains was obtained by applying ultrasonic treatment to the melt at the temperature range between 700 and 740 °C, before pouring. Cavitation-enhanced hetero- geneous nucleation is the mechanism proposed to explain grain refinement by ultrasound in this alloy. Moreover, ultrasonic treatment of the melt was found to lead to cast samples with hardness values similar to those obtained in samples submitted to precipitation hardening, suggesting that ultrasonic treatment can avoid carrying out heat treatment of cast parts.